Impact of Public Private Partnership on the Development of Critical Infrastructure in Nigeria during the Fourth Republic - Edogbanya , Victor Onuh; Adekeye, Joseph Adeshola (Journal of Applied And Theoretical Social Sciences, 2024)
The use of Public Private Partnership (PPP) for the provision of critical infrastructure became imperative in order to reduce cost, absorb risk, improve quality, guarantee effective service delivery and obtain value for money. However, the extent to which the use of PPP in the provision of critical infrastructure in Nigeria during the fourth republic has not been established due to lack of access to necessary data. This is the gap that this study intends to bridge by providing necessary information on the impact of PPP in the development physical infrastructure within the period under review. Therefore, the main objective of the study is to examine the impact of PPP in the development of road, rail and water transportation in Nigeria during the fourth republic. Methodologically, the paper adopts a qualitative approach for the purpose of obtaining the required materials through the contents analysis of documents from the Ministry of Transport, Bureau of Public Enterprises (BPE), Bureau of Public Procurement (BPP), National Bureau of Statistics (NBS) and National dailies. The findings of the study reveal that the impact of PPP in the development of road, rail and water transportation during the fourth republic in Nigeria have not be quite impressive due to poor maintenance culture, poor funding, lack of accountability and evading due process in contract award .Therefore, the study recommends for the use of cost benefit analysis in ensuring value for money, replacement of obsolete equipment, increase in budgetary provision and compliance with the provisions of Public Procurement Act in contract award.